Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(x\cdot15+x+15=463\)
\(x\cdot\left(15+1\right)+15=463\)
\(x\cdot16+15=463\)
\(x\cdot6=463-15\)
\(x\cdot6=448\)
\(x=448:6\)
\(x=\frac{448}{6}\)
\(x=\frac{224}{3}\)
\(x\cdot15+x+15=463\)
\(x\cdot15+x=463-15\)
\(x\cdot15+x=448\)
\(x\cdot\left(15+1\right)=448\)
\(x\cdot16=448\)
\(x=448:16\)
\(x=28\)
x . 15 + x + 15 = 463
x . 15 + x = 463 - 15
x . 15 + x = 448
x . ( 15 + 1 ) = 448
x . 16 = 448
x = 448 : 16
x = 28
x . 15 + x + 15 = 463
x . 15 + x = 463 - 15
x . 15 + x = 448
x . ( 15 + 1 ) = 448
x . 16 = 448
x = 448 : 16
x = 28
3990- (463 x 72 - 39 x 39 ) : 15 =
= 3990 - ( 463 x 72 - 39 x 39 ) : 15
= 3990 - ( 33336 - 1521 ) : 15
= 3390 - 31815 : 15
= 3390 - 2121
= 1269
a/ x - ( 25 - x) = x - 15
=> x - 25 + x = x - 15
=> 2x - x = -15 + 25
=> x = 10
b/ x - 8 = -13 - 8
=> x = -13 - 8 + 8 = -13
c/ x - (-15) = 5 - (-19)
=> x + 15 = 5 + 19 => x = 5 + 19 - 15 = 9
d/ (x + 35) = 2x + 15 + (13 - 4)
=> x + 35 = 2x + 15 + 13 - 4
=> x - 2x = 15 + 13 - 4 - 35
=> -x = -11 => x = 11
e/ 5 - 2x = 15-(-9) - 3x
=> 5 - 2x = 15 + 9 - 3x
=> -2x + 3x = 15 + 9 - 5
=> x = 19
g/ x + 135 = 3x - 15
=> x - 3x = -15 - 135
=> -2x = -150
=> x = -150/ - 2 = 75
a) 35-15+x=70
=> 20+x=70
=> x=50
b) 568-(2x+14)=15
=> 2x+14=553
=> 2x=539
=> x=269,5
c) x-105:21=15
=> x-5=15
=> x=20
d) (x-105)*21=15
=> x-105=5/7
=> x=5/7+105
=> x=740/7
a, 35 - 15 + x = 70 b, 568 - (2.x + 14 )= 15
x = 70 - 35 + 15 2.x + 14 = 568 - 15
x = 50 2.x + 14 =553 => 2.x =553-14=539 =>x=539 : 2 =269.5
c, x - 105 : 21 =15 d, (x - 105) . 21 = 15
x - 105 = 15 x 21 x - 105 = 15 : 21
x - 105 = 315 x - 105 = \(\frac{5}{7}\)
x = 315+105 x = \(\frac{5}{7}\)+ 105
x = 420 x = \(\frac{740}{7}\)
=>X.15+x +15=463.
=>X.(15+1)+15=463
=>X.16+15=463
=>X.16=448
=> X=28